Biodiversity of Arbuscular Mycorrhizal Fungi in South America: A Review - Cofré, María Noelia (2019)
Identification of species is crucial in understanding how diversity changes affect ecosystemic processes. Particularly, soil microbial are key factors of ecosystemic functioning .Among soil microbes, arbuscular mycorrhizal fungi (AMF, phylum Glomeromycota) are worldwide distributed and form symbiotic associations with almost 80% of the vascular plants of the earth, except for one species, Geosiphon pyriformis, which associates with the cyanobacteria Nostoc. AMF comprise around 300 morphologically defined or 350–1000 molecularly defined taxa. Since AMF associate with aboveground community, their occurrence and composition can influence ecosystemic processes either through affecting plant community composition and thus its processes rates, or soil microbial communities, which are directly involved in nutrient cycling. Soil microorganisms are considered a potentially suitable target for studying regional and local effects on diversity. The symbiosis with AMF not only increases nutrient uptake by the plant of mainly phosphorus (P) and nitrogen (N) in exchange for plant-assimilated carbon (C), but also improves the tolerance of plants to various biotic and abiotic stresses such as pathogens, salinity, and drought.